An inexpensive high-temperature optical fiber thermometer. (January 2017) - Moore, Travis J.; Jones, Matthew R.; Tree, Dale R.; Allred, David D.
Abstract: An optical fiber thermometer consists of an optical fiber whose tip is coated with a highly conductive, opaque material. When heated, this sensing tip becomes an isothermal cavity that emits like a blackbody. This emission is used to predict the sensing tip temperature. In this work, analytical and experimental research has been conducted to further advance the development of optical fiber thermometry. An inexpensive optical fiber thermometer is developed by applying a thin coating of a high-temperature cement onto the tip of a silica optical fiber. An FTIR spectrometer is used to detect the spectral radiance exiting the fiber. A rigorous mathematical model of the irradiation incident on the detection system is developed. The optical fiber thermometer is calibrated using a blackbody radiator and inverse methods are used to predict the sensing tip temperature when exposed to various heat sources. Highlights: An inexpensive coating for an optical fiber thermometer sensing tip is tested. Inverse heat transfer methods are used to estimate the sensing tip temperature. An FTIR spectrometer is used as the detector to test the optical fiber thermometer using various heat sources.